Off with Her Head! Who Dares May Lose? NHS Fit for Purpose - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2022)
This article attempts to define, analyse, and resolve a problem. The problem is complex and multi-faceted. it involves an amalgam of intricately connected. bio-psychosocial and political economic factors. Added to which are issues of traditions, reliance, and the emotional familiarity of a well treasured comforter The National Health Service. If the NHS is viewed as a system, the input is inaugurated by the patient who offers symptoms. The general practitioner (GP) makes a diagnosis, a degree of agreement and acceptance is reached, and various options are available to treat the presenting symptoms. However, what if we dig beneath the presenting symptoms and unearth foundational causes perhaps unknown facts of which the practitioner is unaware? Lifestyle causes but which the patient medicalises. Such as reckless spending or driving, — partying, drinking, overeating. Alternatively, maybe the patient, by choosing a career which is beyond the necessary ability, or personality characteristics demanded, by the job or career. Lacking the necessary characteristics such as robustness and tenacity and the ability to cope, without suffering from stress-related diseases. Or living lifestyles beyond sustainable economic means? Originally back in the early days of the NHS, the GP knew the patient more intimately from the cradle onwards, however nowadays the relationship is usually more transparent. Patients cannot count on seeing the same GP for every consultation. And furthermore, the notes written by the GP are less personal and less revealing. In an effort towards transparency patients can read their notes. In the present climate of victimization and litigation, it is perhaps only for the more robust clinicians to use blatant language or face to face confrontation clinically and confront behaviour related to causation. Can the sufferers plead being a victim of ignorance and blame the educational or the welfare system? Medicalization of the results of breakdown and these unsustainable choices then falls on the NHS to care but not notice longer cure? With the word cure, now removed from the aim of the National Health System which some cynics will label as an economic based subtle nevertheless intentional dumbing down of provision. (Harries, Elliott, & Higgins, 1999) NHS England, 2017. This article aims to focus on the dilemma which begs the question: Is it the responsibility of the clinician to alleviate the symptoms or to treat the cause and prevent recurrence or both? Furthermore, is the NHS system too antiquated, to deal with the present-day situation is it no longer fit for purpose.